Genome-Wide Identification, Comprehensive Gene Feature, Evolution, and Expression Analysis of Plant Metal Tolerance Proteins in Tobacco Under Heavy Metal Toxicity - Liu, Jikai; Gao, Yongfeng; Tang, Yunlai; Wang, Dan; Chen, XiaoMing; Yao, Yinan; Guo, Yaoling (Frontiers in Genetics, 2019)
Plant metal tolerance proteins (MTPs) comprise a family of membrane divalent cation transporters that play essential roles in plant mineral nutrition maintenance and heavy metal stresses resistance. However, the evolutionary relationships and biological functions of MTP family in tobacco remain unclear. In the present study, 26, 13 and 12 MTPs in three main Nicotiana species (N. tabacum, N.sylvestris and N. tomentosiformis) were identified, respectively, and were designated based on the orthologous relationship to Arabiodopsis MTPs. The phylogenetic relationships, gene structures, chromosome distributions, conserved motifs and domains of NtMTPs were systematic analyzed. According to the phylogenetic features, 26 NtMTPs were classified into three major substrate-specific groups (Zn-CDFs, Zn/Fe-CDFs and Mn-CDFs) and seven primary groups (1, 5, 6, 7, 8, 9 and 12). All of the NtMTPs contained modified signature sequence and the cation_efflux domain, whereas some of them also harbored the ZT_dimer. Evolutionary analysis showed that NtMTP family of N.tabacum originated from its parental genome of N. sylvestris and N. tomentosiformis, and further underwent gene lost and expanded via one segmental duplication event. Moreover, the prediction of cis-acting elements and the microRNA target sites of NtMTP genes suggested the diverse and complex regulatory mechanisms that control NtMTPs gene expression. Expression profile analysis derived from transcriptome data and quantitative real-time PCR (qRT-PCR) analysis showed that the tissue expression patterns of NtMTPs in the same group were similar but varied among groups, indicating the conserved and essential roles of NtMTP genes in tobacco growth and development. In addition, under heavy metal toxicity, NtMTP genes exhibited various responses in either tobacco leaves or roots. 26 and 20 NtMTPs were found to response to at least one metal ion treatment in leaves and roots, respectively. These results provided a perspective on the evolution of MTP genes in tobacco and were helpful for further functional characterization of NtMTP genes.